Early experience with percutaneous transluminal angioplasty using a vinyl balloon catheter. - Ring, E J (1980)
The technique of transluminal dilatation of arterial stenoses has been greatly facilitated with the recent development of the vinyl balloon catheter by Gruntzig. Since these catheters became available to us in early 1978, we have utilized them to attempt dilatation of 62 arteries, including iliac, femoral and renal vessels. Immediate success was achieved in 57 of these vessels. There were five early complications (two distal embolizations and three prompt occlusions) and three late complications (two restenoses and one occlusion at ten days). The occlusions were all treated promptly surgically with good results and the stenoses redilated. Noninvasive pressure measurements were obtained on all patients whose iliac or femoral arteries were dilated both before and after the procedure, with objective improvement demonstrated by this method. The procedure itself is well tolerated by patients. It involves only minimal discomfort and risk and a markedly shortened hospital stay. The procedure can be easily accomplished by physicians who are thoroughly familiar with routine femoral catheterization techniques and it is believed that this technique will have a definite place in the future therapy of many cases of arterial stenosis.